2022
DOI: 10.1016/j.jvs.2021.07.222
|View full text |Cite
|
Sign up to set email alerts
|

Acute limb ischemia among patients with COVID-19 infection

Abstract: Introduction SARS-CoV-2 infection has been associated with thrombotic complications such as deep vein thrombosis or stroke. Recently, numerous cases of acute limb ischemia (ALI) have been reported although pooled data are lacking. Methods We systematically searched PubMed, Embase, Scopus, and the Cochrane Library for studies published online up to January 2021 that reported cases with SARS-CoV-2 infection and ALI. Eligible studies should have reported early outcomes inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 82 publications
0
29
2
2
Order By: Relevance
“…Tang et al showed that high D-dimer and fibrin degradation product levels were higher in patients who died of COVID-19 infection (8). Ischemia in a healthy non-atherosclerotic artery is rare, but it has been reported in COVID-19 infection (9)(10)(11)(12). The incidence of acute limb ischemia in COVID-19 patients was reported to be about 0.9% (9), which is higher than that in the general population (13) and hospitalized patients with cancer (14).…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al showed that high D-dimer and fibrin degradation product levels were higher in patients who died of COVID-19 infection (8). Ischemia in a healthy non-atherosclerotic artery is rare, but it has been reported in COVID-19 infection (9)(10)(11)(12). The incidence of acute limb ischemia in COVID-19 patients was reported to be about 0.9% (9), which is higher than that in the general population (13) and hospitalized patients with cancer (14).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of hospitalized COVID-19 patients with arterial thrombosis demonstrated a combined mortality rate of 31.4% and a limb loss rate of 23.2% [ 7 , 8 ]. However, De Roquetaillade et al reported that some cases of arterial thrombosis were not prevented by therapeutic levels of anticoagulation [ 9 ]. While most hospitalized patients are placed on DVT prophylaxis, and patients with evidence of thrombus are typically fully anticoagulated, those being treated outpatient for respiratory symptoms are not placed on prophylaxis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Galyfos et al [40] conducted a systematic review on 34 articles regarding acute limb ischemia and SARS-CoV-2 infection, involving 540 patients. Mortality rate among these patients was 31.4%, while in our study, the rate was 13.18% at 1-month follow-up; the amputation rate among the 540 patients in the review was 23.2%, compared with 13.18% in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality rate among these patients was 31.4%, while in our study, the rate was 13.18% at 1-month follow-up; the amputation rate among the 540 patients in the review was 23.2%, compared with 13.18% in this study. In the systematic review by Galyfos et al, the medical treatment was selected in 41.8% of cases, and these had a higher risk of death when compared with any other intervention [40]. With the application of a proper surgical treatment (either open surgery or endovascular) and with a systemic anticoagulant treatment, we think that the patients with acute limb ischemia and SARS-CoV-2 infection who present within the revascularization window can have a good prognosis, despite viral presence as a prothrombotic factor.…”
Section: Discussionmentioning
confidence: 99%